Solar electric ambulance van to assist rural emergencies of Bangladesh- a complete off-grid solution - Tarek, Rahmeen; Anjum, Afra; Abrar-Ul-Hoque, MD.; Rahim, Forkan Abdur (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.